An introduction to trading in the financial markets : technology - systems, data, and networks - Williams, R. Tee. (Amsterdam ; Boston : Academic Press, 2011)
Networks, systems, and data join the financial markets into a single interrelated environment that processes millions of transactions in real time. This volume, the third of four, investigates the interconnected nature of financial markets by examining networks, systems, and data in turn. Describing what technologies do instead of how they work, the book shows how they drive each step of the trading process. We learn why the speed and scope of financial automation are growing, and we observe the increasing importance of data in the regulatory process. Contributing to these explanations are visual cues that guide readers through the material. If knowledge comes from information, then this volume reveals much about the core of the finance industry. Explains how technologies and data make the financial markets one of the most automated industries. Describes how each step in the trading process employs technology and generates information. Presents major concepts with graphs and easily understood definitions.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Financial instruments; Capital market -- Technological innovations; Stock exchanges -- Technological innovations